2019
DOI: 10.2147/ijgm.s184732
|View full text |Cite
|
Sign up to set email alerts
|

Population awareness of coronary artery disease risk factors in Jeddah, Saudi Arabia: a cross-sectional study

Abstract: BackgroundCoronary artery disease (CAD) is a serious cardiovascular disorder affecting middle-aged individuals. It is a major cause of death among adults over the age of 35 years. In Saudi Arabia, CAD is associated with higher mortality rate, and Saudi patients are reported to have significantly higher prevalence of risk factors for CAD than the Western population. Furthermore, as, to date, there is no definite cure for CAD, prevention of the disease and tight control of the known risk factors are the cornerst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Almalki et al, in a recent study from Jeddah, reported a deficient level of awareness of CAD risk factors, DM, smoking, and lack of physical activity were identified by only 12%, 26%, and 39% of participants, respectively [15].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Almalki et al, in a recent study from Jeddah, reported a deficient level of awareness of CAD risk factors, DM, smoking, and lack of physical activity were identified by only 12%, 26%, and 39% of participants, respectively [15].…”
Section: Discussionmentioning
confidence: 96%
“…Participants younger than 18 years of age and who could not or did not complete the survey were excluded. The questionnaire was adapted and modified from a previous survey by Almalki et al [15]. We collected sociodemographic characteristics, assessments of awareness of CAD risk factors, coronary angiography, and CAD treatment.…”
Section: Methodsmentioning
confidence: 99%
“…[ 17 ] There are very few studies conducted in Saudi Arabia to assess public awareness of risk factors of CAD. [ 18 19 ] In this context, our study designed to investigate the prevalence and awareness of risk factors of CAD among the Saudi adult population in the Dawadmi region, Riyadh Province.…”
Section: Introductionmentioning
confidence: 99%
“…5 Prevalence of CAD in the Middle East region has been reported in the range of 5.4% to 13.4%. 6 A report from the Ministry of Health and Prevention (MoHAP) showed the fact that one of the leading causes of mortality in United Arab Emirates (UAE) is cardiovascular disease (CVD). Of all deaths, 22% were due to acute myocardial infarction, 16% due to cerebrovascular disease, 6% due to ischemic heart disease and 5% due to hypertension.…”
Section: Epidemiologymentioning
confidence: 99%